The Optimization Method for Synthesis of 99mTc-Rutin as Potential Radiotracer in The Development of Cancer Drugs From Flavonoid - Widyasari, Eva Maria; Kusumawardhany, Esty; Sugiharti, Rizky Juwita; Sriyani, Maula Eka; Marzuki, Muharam (Indonesian Society for Cancer Chemoprevention, 2019)
Based on the Basic Health Research Data of Ministry of Health's of Indonesia in 2013, mortality rates from malignant and tumor malignancies in Indonesia are still high with prevalence of cancer is about 1.4%. Chemotherapy is still the primary choice in cancer modality that uses chemotherapeutic drugs to eradicate and inhibit the growth of cancer cells; however the cost this treatment is extremely high. Therefore, patient tends to seek alternative treatment such as consuming traditional herbal medicine for cancer treatment. Rutin is one of the attractive phytochemicals flavonoids because of its antioxidant activities. However, as traditional herbal medicine, its effectiveness is not yet been fully established due to the lack of scientific information. A radiotracer can be defined as a specific radiolabeled molecule that monitors the in vivo behaviour of a functional molecule, and can be used to provide biological information in a living system. Hence, to provide pharmacological information of rutin for cancer treatment, we synthesized radiolabeled flavonoid 99mTc-rutin as radiotracer. The aim of the present study is to develop 99mTc-rutin under varying conditions of rutin quantity, reducing agent concentration and incubation time. Labeling studies were performed by changing the selected parameters one by one and optimum labeling conditions were determined. After observing the conditions for maximum labeling efficiency, 99mTc-rutin was obtained with preparation of 700 μg of rutin with addition of 20 μg of SnCl2.2H2O as reductor and 1-3 mCi 99mTcO4- without any incubation. Radiochemical yield of 99mTc-rutin was determined with radio thin layer chromatography which was found 99.28 ± 0.14% and stable up to 4 hour. From the result of this study, the successfully labeled 99mTc-rutin can be used as a reference for following preclinical study. Furthermore radiolabeled 99mTc-rutin is expected as tools in research and development of rutin as cancer drugs from natural product to obtain detailed information its efficacy.Keywords: radiotracer, 99mTc-rutin, cancer, labeled compounds